Retrobulbar Injection of Amphotericin B in Patients With COVID-19 Associated Orbital Mucormycosis: A Systematic Review. Issue 5 (8th August 2022) - Sharifi, Ali; Akbari, Zahra; Shafie'ei, Mohammad; Nasiri, Naser; Sharifi, Meraj; Shafiei, Mohadeseh; Zand, Amin
Abstract : Purpose: Following COVID-19 infection a rising count of rhino-orbito-cerebral mucormycosis is observed, requiring orbital exenteration, a disabling lifetime affecting surgery. One of the potential interventions for globe salvage in these patients is retrobulbar injections of amphotericin B. This study was conducted to review protocols, outcomes, and side effects of retrobulbar injection of amphotericin B in patients with COVID-19 associated rhino-orbito-cerebral mucormycosis (CAM). Methods: The PubMed, Scopus, Web of Science, and Embase databases were searched using a comprehensive string of relevant keywords. All English studies with the confirmed diagnosis of CAM infection were included. We excluded all studies in which retrobulbar injection of amphotericin B was not implemented in any of the patients or there was a lack of clarified and detailed data about this procedure among participants. Results: A total of 647 cases had a history of retrobulbar injection(s) of amphotericin B in 13 reviewed studies with 3, 132 subjects of CAM. The most common protocol was the retrobulbar injection of 1 ml of 3.5 mg/ml liposomal amphotericin B for 3 doses daily or on alternate days. We discerned that the globe salvage rate was 95.0% in eyes with a history of retrobulbar injection(s). The total rate of orbital exenteration was 14.9%, regardless of the history of retrobulbar injection of the drug. Other outcomes of this intervention were vision salvage and reduced major ophthalmic complaints, including pain, swelling, chemosis, ptosis, and ophthalmoplegia. The side effects of this intervention were not serious, and most of them were transient. They included swelling at the injection site, restriction of ocular motilities, exacerbation of orbital inflammation, and even intensification of visual impairment in a few cases. Conclusions: Retrobulbar injection of amphotericin B should be considered a nearly safe and protective intervention against orbital exenteration in patients with CAM. It may also be effective in saving vision. Since the effectiveness of orbital exenteration in the survival of patients is not ascertained, retrobulbar injections can be considered an alternative intervention. Abstract : Retrobulbar injection of amphotericin B is a nearly safe procedure which can lead to eye globe salvage and reducing the rate of orbital exenteration in patients with COVID-19 associated orbital mucormycosis.